If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(2n-4)=(18n-36)
We move all terms to the left:
9(2n-4)-((18n-36))=0
We multiply parentheses
18n-((18n-36))-36=0
We calculate terms in parentheses: -((18n-36)), so:We get rid of parentheses
(18n-36)
We get rid of parentheses
18n-36
Back to the equation:
-(18n-36)
18n-18n+36-36=0
We add all the numbers together, and all the variables
=0
n=0/1
n=0
| 4p+7,90=5p-5 | | 5w+1=3w+13 | | 80-2x=54 | | (4x=6)/2=3x+4 | | y/7+8=15 | | m/2=28 | | 5/a=40 | | 2x–14=x+1 | | 3x+5x=-31-6x | | 9x-99=5x-11 | | Y=2x+6x3 | | 20*15=20x*20x-x^2 | | -1/2x=5/3 | | 16=p/32 | | 8x-2=5(x+3) | | 5=20-x-x(20-x)/x | | 23-4z=3(z-4) | | 16.4+2y=8y+2 | | X⁴-4x²=0 | | 2w+-9=9w+19 | | 300=40x-x^2 | | 6v+13=3v+34 | | 4u+22=7u-8 | | 12=3(h-2) | | 5x-4x=2-3 | | −7x−4−2=8 | | 20=52-4f | | 7(6y+2)=−8 | | 42y+14=-8 | | 3c-2(3-2c)=3c-4c=-1c | | 6(x+8)=4(x-7) | | 3b+5(2b+9)-19=0 |